Dissecting the Genetics of Autism Spectrum Disorders: A Drosophila Perspective - Bellosta, Paola; Soldano, Alessia (Frontiers in Physiology, 2019)
Autism Spectrum Disorder (ASD) is a complex group of multi-factorial intellectual disabilities that arise from the interaction of genetic and non-genetic risk factors. Genetic alterations have been identified in around 20% of ASD patients and the use of genetic models, such as Drosophila melanogaster, has been of paramount importance to decipher the significance of these alterations. In fact, many of the ASD associated genes, such as FMR1, Neurexin, Neuroligins and SHANK encode for proteins that have a conserved function in neurons and during synapsis development, both in humans and in the fruit fly. Drosophila is a prominent model in neuroscience due to the conserved genetic networks that control neurodevelopmental processes and to the easiness of its genetics. In the present review, we will describe recent advances in the field of autism coming from the functional characterization of ASD associated genes in the fruit fly.